Peruvian middle school students and teachers' environmental literacy dimensions - Huamán Pastorelli, Sandra Elizabeth (2020)
The objective of the article has been to determine the relationship that exists between the environmental literacy of the students and their teachers of fifth and sixth grade of primary of the public and private schools of Metropolitan Lima 2019. A survey was applied to 1,396 primary education students, of whom 645 were in the fifth grade and 751 in the sixth grade and its 33 teachers, previously 11 public schools and 7 private schools were selected from all the UGELs of Metropolitan Lima area. According to the results of the research, it was concluded that there is an average level of literacy for students and teachers of 5th and 6th grade of primary education in Metropolitan Lima and a highly significant relationship between the environmental literacy of these students and their teachers , which leads to consider that, if you want to improve the literacy level of students, you must also improve the literacy level of teachers and the teaching of environmental issues be part of the school curriculum.